1999
DOI: 10.1002/j.1550-8528.1999.tb00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight‐Related Attitudes and Behaviors in Fourth Grade American Indian Children

Abstract: . Obes Res. 1999;7:34-42. Objective: American Indian children have a high prevalence of obesity, yet little is known about weight-related attitudes and the prevalence of dieting in this population. This study assessed weight concerns, body size perceptions, weight reduction attempts, and weight loss methods in fourth grade American Indian children. Research Methods and Procedures:attended one of eight schools in the Pathways Feasibility Study. Question and answer choices were read to children by trained staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 35 publications
6
40
0
Order By: Relevance
“…Within female groups we found ethnic group differences similar to those reported previously by others (e.g., Caradas et al, 2001;Stevens et al, 1999;Yates et al, 2004). Thus, it appears that although they are thinner than other female groups in this study, White females are less likely to want to be larger, are equally or more dissatisfied with their current body size, and are equally likely to be engaging in risky weight control behaviors than their non-White peers.…”
Section: Bmi and Ed Risksupporting
confidence: 88%
See 2 more Smart Citations
“…Within female groups we found ethnic group differences similar to those reported previously by others (e.g., Caradas et al, 2001;Stevens et al, 1999;Yates et al, 2004). Thus, it appears that although they are thinner than other female groups in this study, White females are less likely to want to be larger, are equally or more dissatisfied with their current body size, and are equally likely to be engaging in risky weight control behaviors than their non-White peers.…”
Section: Bmi and Ed Risksupporting
confidence: 88%
“…The fact that a strong binge-purge association was not found for Native American girls, may suggest that Native girls are less likely to develop bulimic symptoms. However this is merely speculation at present, since no studies of prevalence rates for clinical eating disorders among Native Americans are currently available.Within female groups we found ethnic group differences similar to those reported previously by others (e.g., Caradas et al, 2001;Stevens et al, 1999;Yates et al, 2004). Thus, it appears that although they are thinner than other female groups in this study, White females are less likely to want to be larger, are equally or more dissatisfied with their current body size, and are equally likely to be engaging in risky weight control behaviors than their non-White peers.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…We also showed that children trying to lose weight were 7.75 times more likely to be obese. Other studies have shown that obese children are more aware of their weight status and a high proportion of them wanted or attempted to lose weight [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Parental self-efficacy about childhood obesity was measured by the following question: “How much control do parents have over how much their child weighs?” with Likert-type response options of “a lot,” “a little,” “none,” and “don’t know.” Line drawings of boys and girls were adapted from a previous instrument32 and used to further elucidate parental health beliefs. As shown in Figure 2, the 6 line drawings depict children whose appearance range from relatively thin (C) to markedly obese (H).…”
Section: Methodsmentioning
confidence: 99%